SOLIDARITAS SOSIAL KELOMPOK NELAYAN ABBOKOANGE DESA KUPA - Fadilla, Rasna; Sakaria Anwar; Buchari Mengge (SOSIORELIGIUS, 2024)
This article explains the social solidarity of the Abbokoange fishermen group, Kupa Village, Mallusetasi District, Barru Regency. The approach used in this study is a descriptive approach. To collect data, the author uses primary data from interviews, both structured and in-depth (in-depth interviews), as well as direct observation. The results of this study indicate that the social solidarity that occurs in the Abbokoange fishermen group in Kupa Village is woven from every fishing activity, namely in production activities or fishing activities at sea, distribution or marketing activities, and also in daily life.